2023
DOI: 10.31219/osf.io/pq5ac
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pemerolehan Bahasa Kedua (Bahasa Inggris) pada Anak Usia 5 tahun melalui Media Youtube

Abstract: Periode emas menjadi salah satu bagian penting dalam pemerolehan bahasa. Pengaruh lingkungan dan pola asuh akan berimbas terhadap perkembangan bahasa, kognitif, psikomotor, kepribadian maupun sosial. Berbagai macam video, mulai dari film, music, serial TV dimuat dalam media sosial Youtube. Pengaturan yang ada pada Youtube juga dapat disesuaikan dengan usia dari penikmatnya. Youtube menyediakan fitur YoutubeKids bagi pengguna yang memang berada di bawah umur. Video-video yang ditonton oleh anak-anak akan mensti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…And also research that has been conducted by Muhammad Edo Fadhli (Fadhli, 2023). The study found that foreign language acquisition (English) that occurred in child "A" was strongly influenced by videos watched through Youtube social media.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…And also research that has been conducted by Muhammad Edo Fadhli (Fadhli, 2023). The study found that foreign language acquisition (English) that occurred in child "A" was strongly influenced by videos watched through Youtube social media.…”
Section: Introductionmentioning
confidence: 95%
“…However, YouTube media does not fully substitute the role of humans in language acquisition or learning. Furthermore, the next research was conducted by Addinda Fardischa (Addinda Fardischa, 2020). The study found that the subject's English second language ability can be seen from his understanding of the movie he watched.…”
Section: Introductionmentioning
confidence: 99%
“…Language learning and language acquisition are often separated. The processes when a youngster picks up a second language after mastering their first are connected to language acquisition (Alwi, 2021). Consequently, language learning concerns the second language, while language acquisition concerns the first language.…”
Section: Introductionmentioning
confidence: 99%